Archaeology of the Central Mississippi Valley - Morse, Dan F. (Book collections on Project MUSE., 2009)
A classic work detailing an 11,000-year period of human culture within the largest river system of North America. The earliest recorded description of the Central Mississippi Valley and its inhabitants is contained within the DeSoto chronicles written after the conquistadors passed through the area between 1539 and 1543. In 1882 a field agent for the Bureau of American Ethnology conducted the first systematic archaeological survey of the region, an area that extends from near the mouth of the Ohio River to the mouth of the Arkansas River, bounded on the east by the Mississ.